Developing practice capability : transforming workplace learning - Patton, Narelle (Higher education horizons, 2018)
Developing Practice Capability: Transforming Workplace Learning explores a Crucible Model for Professional Development as a means for better understanding workplace learning as a place for capability development. Professional practice is presented as a dynamic phenomenon that is embedded in practice contexts, embodied in and transformed through individual performances and ethically grounded. Workplace learning is examined in relation to development of a broad range of capabilities including qualities, judgement and potential for ethical action. The potential of the Crucible Model to enhance workplace learning is explored and narratives of professional practice capability development in action are provided. The discussions generate a range of implications and recommendations for workplace learning relevant to workplace learning educators and supervisors, academic educators, practitioners and students.